When you multiply two numbers which have the same sign the answer is positive. Therefore multiply eight and three to get 24 and the answer is positive; therefor the answers 24.
Answer: x = 1
Step-by-step explanation:
Simplifying
-4(-6x + 3) = 12
Reorder the terms:
-4(3 + -6x) = 12
(3 * -4 + -6x * -4) = 12
(-12 + 24x) = 12
Solving
-12 + 24x = 12
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '12' to each side of the equation.
-12 + 12 + 24x = 12 + 12
Combine like terms: -12 + 12 = 0
0 + 24x = 12 + 12
24x = 12 + 12
Combine like terms: 12 + 12 = 24
24x = 24
Divide each side by '24'.
x = 1
Simplifying
x = 1
Answer:
y = -2
Step-by-step explanation:
Any asymptotes of a rational function will be described by the quotient of the numerator and denominator (excluding any remainder).
![f(x)=\dfrac{-2x}{x+1}=-2+\dfrac{2}{x+1}](https://tex.z-dn.net/?f=f%28x%29%3D%5Cdfrac%7B-2x%7D%7Bx%2B1%7D%3D-2%2B%5Cdfrac%7B2%7D%7Bx%2B1%7D)
The horizontal asymptote is ...
y = -2
Answer:
s = 1
Step-by-step explanation:
4s + 6s - 4 = 6
10s - 4 = 6
+ 4 +4
10s = 10
10s/10=
s = 1
Hope this helps! If you have any additional questions please don't hesitate to ask me or your teacher to be sure you master the subject. :) Stay safe and please mark brainliest!
Answer:
28 days
Step-by-step explanation:
because the frog climbs 3m in the day, but falls 2m at night, it technically climbs 1m every 24 hours. this means after the 1st day, it will have climbed a total of 1m, on the second, it will have climbed a total of 2m, and so on. however, when it gets nearer to the top, that's when things start to change. after the 26th day, it will have climbed 26m. on the 27th day, it will be 27m, but then when it jumps 3m the next day, it will reach 30m total before it falls during the night and it will be able to get out of the hole.
i hope this helps! :)